2015
DOI: 10.1007/s10735-015-9614-7
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression and prognostic role of EHD2 in human breast carcinoma: correlation with E-cadherin

Abstract: Decreased expression of epithelial cadherin (E-cadherin) has been noted to associate with aggressiveness and metastasis of breast cancer. The aim of this study was to examine the effect of C-Terminal EH domain-containing protein 2 (EHD2) expression on E-cadherin and related mechanism in the metastasis of breast cancer. Immunohistochemical analysis was performed in 96 human breast carcinoma samples and the data were correlated with clinicopathologic characteristics. Furthermore, Western blot analysis was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
5
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 24 publications
5
20
5
1
Order By: Relevance
“…4A ), indicating that the RCN1/PIGX/RCN2 complex would regulate the expression of these genes. Among these genes, ZIC1 and EHD2 were recently suggested to have a function related to human tumorigenesis ( 25 30 ). The upregulation of these potential downstream genes was validated with qRT-PCR ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4A ), indicating that the RCN1/PIGX/RCN2 complex would regulate the expression of these genes. Among these genes, ZIC1 and EHD2 were recently suggested to have a function related to human tumorigenesis ( 25 30 ). The upregulation of these potential downstream genes was validated with qRT-PCR ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Abundant research has identified various tumor-derived secreted factors, including S100A8, S100A9, VEGF and Angpt2, important in premetastatic microenvironment formation in different tumor models (Shi et al 2015). Calprotectin S100A8 and S100A9 have been reported in association with tumor progression and metastasis, and these two proteins also possess a pivotal influence on chronic inflammation (Lukanidin and Sleeman 2012).…”
Section: Every Step During Metastasis Involves Interactions Between Tmentioning
confidence: 99%
“…The level of the first protein, which belongs to the EHD family associated with plasma membrane, has been reported to be reduced in human esophageal squamous carcinoma in comparison with adjacent normal tissues, linked to increased motility of the tumor cells [ 49 ]. Subsequently, a decreased expression was also observed, correlated with histological grade, in an immunohistochemical study of 96 human breast carcinoma samples, leading Shi et al to suggest that this protein inhibits metastasis by regulating EMT [ 50 ]. The second protein, which belongs to the small GTPase family Rab and to the Rab5 subfamily, presents an estrogen receptor-responsive element in its promoter region which can be dysregulated in breast cancer cells, the consequences of this key finding in cancer research having been reviewed by Chua and Tang [ 51 ].…”
Section: Discussionmentioning
confidence: 99%